Analisis Hubungan Safety Climate terhadap Driver Behavior Operator Forklift pada Perusahaan Manufaktur: Indonesia - Fatihul Azzam, Ahmad; Kurniasih, Dewi; Rachman, Farizi (JURNAL UNITEK, 2025)
Forklifts are loading and unloading vehicles that have recorded the highest number of near-miss incidents, primarily caused by human error and classified as unsafe behavior. In this context, driver behavior associated with the safety climate within the manufacturing company refers specifically to forklift operators. This study divides the safety climate into six variables: communication and procedures, job pressure, management commitment, relationships, safety regulations, and risk perception. The aim of this research is to analyze the relationship between safety climate and driver behavior among forklift operators in a manufacturing company. Data were collected using a questionnaire instrument with a total sample of 37 participants. The relationship was examined using the Pearson Product Moment Correlation test. The results show that communication and procedures have a moderate correlation with driver behavior (p-value = 0.544), while job pressure (p-value = 0.642), management commitment (p-value = 0.762), relationships (p-value = 0.712), and safety regulations (p-value = 0.607) show strong correlations. Risk perception also shows a moderate correlation (p-value = 0.544). These findings indicate that all six safety climate variables—communication and procedures, job pressure, management commitment, relationships, safety regulations, and risk perception—are significantly related to driver behavior.